2010
DOI: 10.1111/j.1464-410x.2009.08954.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection rate and factors predictive the presence of prostate cancer in patients undergoing ultrasonography‐guided transperineal saturation biopsies of the prostate

Abstract: Study Type – Diagnostic (case series)
Level of Evidence 4 OBJECTIVES To assess the prostate cancer detection rate and predictive factors for prostate cancer after transrectal ultrasonography (TRUS)‐guided transperineal saturation re‐biopsies of the prostate, using a 24‐core scheme. PATIENTS AND METHODS We evaluated 143 consecutive patients undergoing TRUS‐guided transperineal saturation re‐biopsy of the prostate using a 24‐core scheme. The inclusion criteria were a previous negative biopsy and a prostate‐speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…Some studies have shown that prostate volume is a relevant variable for the detection of PC [32,33,34]. Uzzo et al [35] have reported a PC detection rate of 23% in prostates ≥50 ml and 38% in prostates <50 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that prostate volume is a relevant variable for the detection of PC [32,33,34]. Uzzo et al [35] have reported a PC detection rate of 23% in prostates ≥50 ml and 38% in prostates <50 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Novara et al. [6] summarised published reports and showed that the cancer detection rate was similar among different series and approaches. The overall detection rate ranged from 14 to 45% for the transrectal approach and from 23 to 42% for the transperineal approach in men without and up to three previous negative biopsy series.…”
Section: Introductionmentioning
confidence: 97%
“…There has been no general agreement regarding the number of cores and the optimal approach. In addition, we noticed that there was no specific relationship between the method used and the cancer detection rates (4,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) (Table IV).…”
Section: Discussionmentioning
confidence: 99%